Univalency of general integral operator defined by Schwarz functions - B.A. Frasin (Journal of the Egyptian Mathematical Society, 2013)
In this paper, we obtain new univalence conditions for the integral operator Wβ(z)=β∫0ztβ-1∏i=1n(1+wi(t))γiexp∑i=1nγiwi(t)dt1β, where wi(t) are Schwarz functions defined in the open unit disk. Our main results contain some interesting corollaries as special cases.